Antitumor effects of metformin are a result of inhibiting nuclear factor kappa B nuclear translocation in esophageal squamous cell carcinoma. Issue 4 (26th February 2018) - Sekino, Nobufumi; Kano, Masayuki; Matsumoto, Yasunori; Sakata, Haruhito; Akutsu, Yasunori; Hanari, Naoyuki; Murakami, Kentaro; Toyozumi, Takeshi; Takahashi, Masahiko; Otsuka, Ryota; Yokoyama, Masaya; Shiraishi, Tadashi; et al.
Abstract : Esophageal squamous cell carcinoma (ESCC) is an intractable digestive organ cancer that has proven difficult to treat despite multidisciplinary therapy, and a new treatment strategy is demanded. Metformin is used for type 2 diabetes mellitus and its antitumor effects have been reported recently. Metformin exerts antitumor effects in various respects, such as inhibiting inflammation, tumor growth and epithelial‐mesenchymal transition (EMT). However, few reports have described the efficacy of metformin on ESCC, and their findings have been controversial. We analyzed the antitumor effects of metformin and clarified its effects on anti‐inflammation, growth suppression and EMT inhibition. Activation of nuclear factor kappa B (NF‐κB), the major transcription factor induced by inflammation, was investigated by immunostaining. We found that localization of NF‐κB in the nucleus was reduced after metformin treatment. This suggests that metformin inhibited the activation of NF‐κB. Metformin inhibited tumor growth and induced apoptosis in ESCC cell lines. Associated with EMT, we examined cell motility by a wound healing assay and the epithelial marker E‐cadherin expression of various ESCC cell lines by western blotting. Metformin inhibited cell motility and induced E‐cadherin expression. In conclusion, metformin showed multiple antitumor effects such as growth suppression, invasion inhibition, and control of EMT by inhibiting NF‐κB localization on ESCC. Further exploration of the marker of treatment efficacy and combination therapy could result in the possibility for novel treatment to use metformin on ESCC. Abstract : Metformin, which is used for type 2 diabetes mellitus, showed antitumor effects by inhibiting cell proliferation, tumor growth and EMT in esophageal squamous cell carcinoma. These effects might have been induced by inhibiting NF‐κB activation.